Evaluasi nilai ekspor dan impor regional Association of Southeast Asian Nations Sebelum dan setelah Krisis ekonomi tahun 1998 - Agus Eko Sujianto; Sokib Sokib (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2017)
The purposes of this research are to evaluate the difference of export value of ASEAN member countries before and after economic crisis in 1998 and to evaluate the difference of import value of ASEAN member countries before and after economic crisis in 1998. While export and import become the main variable of research this sekgus is an important component of the preparation of the trade balance. The research data used secondary data of export and import in 1982-1997 (period before economic crisis in 1998) and 1999-2014 (period after economic crisis in 1998) from annual publication of ADB. Based on the Paired Sample t-Test test it can be argued that: the export value of ASEAN member countries before and after the crisis differed significantly and the import value of ASEAN member countries before and after crisis differed significantly